(3eSfO GdOQGeis - (3YHO Gddg Hf YHO GdQMef Hf GdaVd Hf HgQGe GdJejej GdOGQej GdSeQbfOj, CHh eMeO,J (B255 (3g` s
(3ChdgG (B:s
(3Udi Gddg Ydjg hSde ef bGe s
(3BNQgG (B:s
(3jfJgi HHGH cQGgjI GdEdMGf aj GdbQBf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B95 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B71s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1682s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdMOjK h GdeUWdMs